HIV/AIDS in the elderly: epidemiological impact and associated risk factors in the State of Piauí, Brazil (Research, Society and Development, 2020)
The objective of the present study was to determine the prevalence, epidemiological and socioeconomic profile and risk factors associated with HIV-1 infection in elderly patients diagnosed with HIV/AIDS in the state of Piauí, Brazil. A total of 805 individuals seen at the Central Laboratory of Public Health of Piauí were included. The subjects were classified into two groups: a group of individuals 18 to 59 years old and a group of those 60 years or older. These individuals were tested for HIV-1 infection (ELISA), which was monitored by TCD4+/CD8+ lymphocyte count (flow cytometry) and viral load quantification (branched DNA method), and for coinfections with HBV, HCV and HTLV-1/2 (ELISA and PCR). They also answered an epidemiological questionnaire on socio-demographic, epidemiological and clinical characteristics. The frequency of HIV-1 infection in elderly patients was 3.7% (30/805). The majority of patients were male (66.6%), had a primary school education level (90%), were married (40%) and had a family income of 1 to 4 times the minimum wage (63.3%). The main behavioral risk factors associated with these individuals included lack of condom use (100%) and a history of Sexual Transmitted Diseases – STI (53.3%), surgery (63.3%) or blood transfusion (40%). The elderly patients also had a higher frequency of HIV-HTLV-1/2 co-infection (13.3%). Identifying the main characteristics related to HIV infection in the elderly is important to show that these individuals are also susceptible to HIV-1 infection and must be made aware of risk behaviors.